THE EFFECT OF WRITING ANXIETY ON WRITING PROFICIENCY AT UNIVERSITY STUDENTS - Arisman, Rizal (English Education Journal, 2024)
The purpose of this study was to determine the effect of writing anxiety on writing ability among fourth semester students of English Education Study Program of Dayanu Ikhsanuddin University. This study uses a quantitative approach by applying the ex-post facto method of comparative causal design. The population of this study were all fourth semester students of English Education Study Program which amounted to 120 people. The sample of this research was 31 students who were selected using cluster random sampling technique. The research instruments were questionnaires and tests. The results obtained an R value of 0.060 which is classified as a low category. This means that there is a positive and very low relationship between writing anxiety and writing ability. Thus, based on the research findings and data analysis, it can be concluded that there is no significant influence between speaking anxiety and writing ability at Dayanu Ikhsanuddin University.